KOMPOSISI DAN KELIMPAHAN JENIS IKAN AIR TAWAR PADA LAHAN GAMBUT DIWILAYAH PROPINSI RIAU - Haryono, Haryono (Research Center for Biology-Indonesian Institute of Sciences, 2007)
A study of fish community on peat swamp areas was conduct in Siak and Peialawan, Riau Province. The aims of study are to know species composition/fish diversity, abundance, local distribution, potency, status and habitat types. The results were recorded 23 species belongs to 16 genera and 11 families.Cyprinid is dominant family with 6 species, Belontia hasselti is the most abundant and widest distributed, almost all species are belongs to ornamental fish; 4 endemic species were found.The habitat consist of three types.